Analisis rasio profitabilitas pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia - Imahanani, Hilda; Suwaidi, Rahman Amrullah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Profitability shows the financial performance of bank to measure the success and efficiency of bank in carrying out bank activities and generating profits. Risk management is needed to reduce uncertainty for bank profitability to be successful and efficient. This study examines the effect of capital adequacy, credit distribution, and non-performing loans on profitability in banks listed on the Indonesia Stock Exchange. This study uses a purposive sampling method to select a sample of 38 banks using the 4-years observation method (2017-2020). This analysis used is secondary data from the bank’s annual report. Multiple linier regression was used with quantitative data as technical analysis. Based on the findings of this study, the capital adequacy ratio (CAR) contributes to profitability (ROA), the loan to deposit ratio (LDR) does not contribute to profitability (ROA), and the ratio of non-performing loans (NPL) contributes to profitability (ROA).